A tumor microenvironment (TME)-responsive nanoplatform for systemic saporin delivery and effective breast cancer therapy. Issue 20 (15th February 2021) - Shen, Qian; Xu, Lei; Li, Rong; Wu, Guang; Li, Senlin; Saw, Phei Er; Zhou, Yusheng; Xu, Xiaoding
Abstract : A robust TME pH-responsive nanoplatform was herein developed. This nanoplatform could significantly improve intracellular delivery of cytotoxic saporin to achieve an effective inhibition of tumor growth of breast cancer. Abstract : Intracellular delivery of therapeutic proteins remains a challenge for the success of protein-mediated disease treatment. We herein develop a robust nanoplatform made with a TME-pH responsive Meo-PEG- b -PPMEMA polymer and a cationic lipid-like compound G0–C14 for in vivo delivery of cytotoxic saporin and breast cancer therapy. This nanoplatform could respond to a TME pH to rapidly release saporin/G0–C14 complexes, which could significantly improve the uptake of cytosolic saporin by tumor cells and subsequent endosomal escape, thereby leading to an effective inhibition of tumor growth.